Inkendaal Paediatric Partial Day Hospitalisation - Bellemans, Koen; Van Rossem, Els; Haan, Jurn (International journal of integrated care, 2023)
Inkendaal Rehabilitation Hospital is a neurorehabilitation hospital in Flanders (Belgium) with 178 in-patient beds subserving 15 defined rehabilitation trajectories for adults and children. The rehabilitation trajectories are also organised within an outpatient department for adults and children. The children's outpatient department offers an integrated programme that includes education, interdisciplinary therapy and care. The target groups of the outpatient paediatric operation are children with acquired brain injury, cerebral palsy, neuromuscular disorders, spinal cord disorders, autism spectrum disorder, other developmental disabilities and deconditioning following a period of intensive care or long-term hospitalisation. Within the paediatric partial day hospitalisation, intensive, transdisciplinary rehabilitation is offered in combination with care and education, for children and adolescents with complex rehabilitation needs, whose development as well as school and societal participation is at risk. Management and care are designed and delivered within the ICF-framework. The partial day hospitalisation for children and adolescents accommodates 80 children aged, every year, 1 to 12 and 16 adolescents aged 13 to 18. An average of 80 children attends daily. The children attend the partial day hospitalisation and hospital school daily for a full school year or two school years. Funding is from the rehabilitation hospital budget (BRZ) by the federal government of Belgium, supplemented by federal hospital nomenclature for monodisciplinary services. However, the BRZ only provides funding for 60. Through intensive collaboration between the Ministries of Care, Health and Education, financial resources can be pooled (infrastructure), staff deployment can be handled flexibly and a transdisciplinary rehabilitation offer can be pursued throughout the school day. The children spend the entire school day in a rehabilitation class with their regular class instructor. The different disciplines (nursing, teaching, rehabilitation: speech and language, physical, occupational therapy) pursue the shared objectives with a child (as determined in discussion with the child and family) during individual therapy, group therapy or in the classroom with the teacher, based on the needs of the child and the parents, and taking the environment in to account. In this way, efforts are made to increase the child's opportunities for participation in order to achieve social integration, optimal educational opportunities and increased self-reliance. In the evening, the children return home, so that the home context can also be mobilised and involved in the pursuit of the child's rehabilitation goals. Every 3 months, there is a team meeting and a meeting with the parents to monitor progress with respect to the goals and requests for help, and eventual update of the goals. Medical follow-up can be provided on the service by the presence of a paediatric neurologist and nursing staff.